2020
DOI: 10.1002/jcp.30075
|View full text |Cite
|
Sign up to set email alerts
|

TSPO ligand FGIN‐1‐27 controls priapism in sickle cell mice via endogenous testosterone production

Abstract: Priapism, a prolonged penile erection in the absence of sexual arousal, is common among patients with sickle cell disease (SCD). Hypogonadism is also common in patients with SCD. While the administration of exogenous testosterone reverses hypogonadism, it is contraceptive. We hypothesized that the stimulation of endogenous testosterone production decreases priapism by normalizing molecular signaling involved in penile erection without decreasing intratesticular testosterone production, which would affect ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…In CC from SCD mice and patients, low NO production is related to decreased eNOS activity [ 7 , 28 , 29 ]. Oxidative stress is also amplified in the SCD penis due to upregulation of expression of NADPH oxidase subunit gp91phox and eNOS uncoupling [ 6 , 11 , 29 ]. Therefore, we evaluated the treatment with RVT-FxMe on functional alterations of erectile function in two murine models that display low NO-cGMP bioavailability and elevated oxidative stress, SCD and eNOS -/- mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In CC from SCD mice and patients, low NO production is related to decreased eNOS activity [ 7 , 28 , 29 ]. Oxidative stress is also amplified in the SCD penis due to upregulation of expression of NADPH oxidase subunit gp91phox and eNOS uncoupling [ 6 , 11 , 29 ]. Therefore, we evaluated the treatment with RVT-FxMe on functional alterations of erectile function in two murine models that display low NO-cGMP bioavailability and elevated oxidative stress, SCD and eNOS -/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…In SCD and eNOS gene-deficient (eNOS -/- ) mice CC, low NO-cGMP bioavailability is associated with PDE5 downregulation [ 6 , 10 12 ]. In fact, experimental studies have shown that in vitro NO signaling stimulation induced by ACh and electrical-field stimulation results in increased cavernosal relaxations in SCD and eNOS -/- mice due PDE5 downregulation [ 6 , 7 , 11 , 13 ]. The in vitro addition of the vasoactive agent adenosine also produces exacerbated CC relaxation in SCD mice [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transduceosome is an ensemble of mitochondrial and cytosolic proteins responsible for cholesterol translocation from intracellular stores to the inner mitochondrial membrane ( 72 ). Translocator protein (TSPO) is a high-affinity drug- and cholesterol-binding mitochondrial protein, and its protein expression is decreased in the testis of SCD mice ( 73 , 74 ). The TSPO-dependent import of StAR into mitochondria and the association of TSPO with the outer/inner mitochondrial membrane contact sites drives intramitochondrial cholesterol transfer and subsequent steroid formation ( 73 ).…”
Section: Endogenous Mechanism-specific Molecular Targets For Testoste...mentioning
confidence: 99%
“…Treatment of SCD mice with TSPO-selective drug ligand N,N-dihexyl-2-(4-fluorophenyl) indole-3-acetamide (FGIN-1-27) produces eugonadal levels of testosterone. Normalized testosterone levels corrects priapism without decreasing intratesticular testosterone production ( 74 ). At the molecular level, TSPO ligand, by normalizing testosterone levels, restores PDE5 activity and decreases NOX-mediated increase in oxidative stress in the penis.…”
Section: Endogenous Mechanism-specific Molecular Targets For Testoste...mentioning
confidence: 99%